Parents' and neonatal healthcare professionals' views on barriers and facilitators to parental presence in the neonatal unit: a qualitative study - Stephanie Vanessa Schmid; Christine Arnold; Sophie Jaisli; Benedikt Bubl; Erika Harju; André Kidszun (BMC, 2024)
Abstract Background Parent and infant separation in the neonatal unit is associated with adverse health outcomes. Family-integrated care has several advantages and the potential to reduce these adverse outcomes but requires parental presence. This study aimed to explore the views of parents and neonatal healthcare professionals (nHCPs) on barriers and facilitators to parental presence in a Swiss neonatal unit and to identify possible differences between nHCPs and parents, and between mothers and fathers. Methods Data were collected through semi-structured interviews with parents and focus group discussions with nHCPs. Inductive content analysis was used to identify barriers and facilitators to parental presence in the neonatal unit. Results Twenty parents (10 mothers and 10 fathers) and 21 nHCPs (10 nurses and 11 physicians) participated in the study. Parents and nHCPs experienced barriers and facilitators related to: (1) Structural factors of the institution, such as infrastructure or travel and distance to the neonatal unit. (2) Organization and time management of parental presence, daily activities, and work. (3) Resources, which include factors related to the legal situation, support services, family, and friends. (4) Physical and psychological aspects, such as pain, which mainly affected mothers, and aspects of emotional distress, which affected both parents. Self-care was an important physical and psychological facilitator. (5) Parent-professional interaction. Parental presence was influenced by communication, relationship, and interaction in infant care; and (6) Cultural aspects and language. Some perspectives differed between mothers and fathers, while the overall views of parents and nHCPs provided complementary rather than conflicting insights. Using visit plans to support the organization, educating nHCPs in knowledge skills and available resources to improve encouragement and information to parents, strengthening parent self-care, and improving nHCPs' attitudes towards parental presence were seen as possible improvements. Conclusions Multifactorial barriers and facilitators determine parental presence and experience in the neonatal unit. Parents and nHCPs made specific recommendations to improve parental presence.